2019
DOI: 10.1103/physrevd.100.094505
|View full text |Cite
|
Sign up to set email alerts
|

A2 asymmetry in lattice SU(2) gluodynamics at

Abstract: We study numerically the chromoelectric-chromomagnetic asymmetry of the dimension two A 2 gluon condensate at T > T c in the Landau-gauge SUð2Þ lattice gauge theory with a particular emphasis on finitevolume effects. We show that previously found so called symmetric point at which asymmetry changes sign is an artifact of the finite volume effects. We find that with increasing temperature the asymmetry decreases approaching zero value from above in agreement with the perturbative result.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…in Refs. [6,9]; the definitions of vector potentials A µ (x), and the description of gauge-fixing procedure as well as the expressions for the longitudinal D L (p) and transverse D T (p) gluon propagators -in Refs. [3,11,13].…”
Section: Designations and Lattice Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…in Refs. [6,9]; the definitions of vector potentials A µ (x), and the description of gauge-fixing procedure as well as the expressions for the longitudinal D L (p) and transverse D T (p) gluon propagators -in Refs. [3,11,13].…”
Section: Designations and Lattice Settingsmentioning
confidence: 99%
“…Nevertheless, our conclusion of the critical behavior of the propagator presenrted in Refs. [9][10][11] holds true because it is based on the assumption of the smooth dependence of the conditional average hD(⌧)i P on P, no assumptions on its variance are made. Therewith, the regression curve can be extracted from the data only with a limited precision, therefore, the concept of smoothness should be formulated for the corridor of errors rather than for the proper function.…”
Section: Finite-volume Effects and Properties Of The Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…in Refs. [6,9]; the definitions of vector potentials A µ (x), and the description of gauge-fixing procedure as well as the expressions for the longitudinal D L (p) and transverse D T (p) gluon propagators -in Refs. [3,11,13].…”
Section: Designations and Lattice Settingsmentioning
confidence: 99%
“…Recently, it was demonstrated that correlations between the Polyakov loop and the zeromomentum longitudinal propagator considerably facilitate the analysis of its critical behavior both in the SU(2) [9,10] and SU(3) [11] gluodynamics. This made it possible to describe critical behavior of the asymmetry and the propagator with unprecendented precision.…”
Section: Introductionmentioning
confidence: 99%